2021
DOI: 10.1063/5.0038269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited-state dynamics of SnSe2–SnSe composite thin film

Abstract: We report the ultrafast carrier dynamics of an SnSe2–SnSe composite thin film (∼150 nm thick) deposited using thermal evaporation of in-house synthesized SnSe2 powder. Raman and UV–visible spectroscopy supports the optical properties (direct and indirect bandgaps of 1.86 eV and 0.96 eV, respectively). Ultrafast transient spectroscopy is used to study the charge excited state dynamics in the SnSe2–SnSe composite thin film in the femtosecond to nanosecond interval. An energy model has been proposed based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…According to this fact along with the good match of the GSB signal peak with the band gap energy estimated from the absorption spectrum, we believe that the GSB kinetics in shorttime TA measurements more likely reflect the relaxation of free charge-carriers near the band edges. Therefore, our synthesized SnSe MFs are expected to exhibit a carrier lifetime of ∼6.2 ps, which is comparable to the value reported by Kumar et al 48 The slowly emergent and long-lived GSB signal observed in long-time TA measurements could originate from several sources, including charge-carriers localized to shallow traps, or possibly from the formation of small polarons. 49 Further detailed investigations into the defect chemistry, deformation potential, and carrier-phonon coupling in SnSe are needed to elucidate the precise mechanism for the long-lived long-time GSB decay.…”
Section: ■ Introductionsupporting
confidence: 86%
“…According to this fact along with the good match of the GSB signal peak with the band gap energy estimated from the absorption spectrum, we believe that the GSB kinetics in shorttime TA measurements more likely reflect the relaxation of free charge-carriers near the band edges. Therefore, our synthesized SnSe MFs are expected to exhibit a carrier lifetime of ∼6.2 ps, which is comparable to the value reported by Kumar et al 48 The slowly emergent and long-lived GSB signal observed in long-time TA measurements could originate from several sources, including charge-carriers localized to shallow traps, or possibly from the formation of small polarons. 49 Further detailed investigations into the defect chemistry, deformation potential, and carrier-phonon coupling in SnSe are needed to elucidate the precise mechanism for the long-lived long-time GSB decay.…”
Section: ■ Introductionsupporting
confidence: 86%
“…36,37 The fabrication of SnSe thin films has also engrossed researchers' interest due to a wide variety of applications. [38][39][40][41][42][43][44] Burton et al 45 reported the first thermoelectric generator based on a SnSe film as p-type and Ag as n-type legs with an output power of 0.09 mW (at 618 K) by the thermal evaporation method. A pure SnSe thin film exhibits a very low ZT of 0.055 at 501 K. A further enhancement in ZT is reported by Burton et al 35 using a 3D printing technique.…”
Section: Introductionmentioning
confidence: 99%
“…The intense peaks at 108 and 169 cm −1 for the LBL‐SnSe 2 @MXene belong to E g and A 1g modes of SnSe 2 respectively. [ 49 ] Compared with pure SnSe 2 , the A 1g peak of LBL‐SnSe 2 @MXene slightly shifts toward a lower wavenumber, which is probably caused by the anharmonic effect and interfacial strain between SnSe 2 and MXene. [ 50,51 ] In addition, the peaks at 413 and 617 cm −1 are assigned to the Ti–C bond of MXene.…”
Section: Resultsmentioning
confidence: 99%